Instagram Marketing Strategy Improvement Of Nyongsqee Using Benchmarking And Analytical Hierarchy Process - Ghaisani, Inten Ayuning; Suhendra, Agus Achmad; Kusmayanti, Ima Normalia (eProceedings of Engineering, 2023)
Abstact-Nyongsqee Management is a modeling agency for artists which in its business activities channel model talent for photo shoots and catwalks as well as acting talent for commercials and film stars. Nyongsqee’s business is currently facing problems, including low marketing activity, low brand awareness, and low Instagram engagement rate. This research is focusing on the promotion as the root of the problem. Based on the assessment of potential solutions, increasing effectiveness of Nyongsqee Instagram is the most effective solution to fix Nyongsqee marketing strategy. Therefore, it’s needed to design the improved content marketing of nyongsqee’s Instagram and more varied content. This research objective is to design the improved content marketing of nyongsqee’s Instagram in order to increase its engagement rate performance. The methodology used in this research is benchmarking and AHP. The sampling technique used were purposive sampling and descriptive sampling. The sample used in this study was 30 for purposive and 100 for descriptive sampling. The study result is a content marketing strategy nyongsqee Instagram in order to improve their overall performance and percentage of its engagement rate. The design of the content marketing strategy starts by story, profile, caption, reels and feeds. Keyword- nyongsqee, benchmarking, analytical hierarchy process, modelling.